Empowerment Community through the Making of Activated Carbon from Coconut Shells as a Filter in Gravity-Fed Filtering System - Zidni Ilman Navia; . Fitriani; Vivi Mardina (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2018)
The community of Alue Ie Puteh Village is a group of people who live in the coastal areas and has problem with the availability of clean water. The lack of water treatment technology becomes an obstacle for the community in water treatment. The objective of this activity is to provide knowledge or understanding to the community about the utilization of activated carbon from coconut shell as filter media in gravity-fed filtering system. The activity was carried out for 3 months from June–August 2017 and consists of several steps: 1) Socialization; 2) Training; and 3) Monitoring and evaluation. The results show that people in the Village of Alue Ie Puteh have been able to apply technique of producing the activated carbon from coconut shell as filter media in gravity-fed filtering system. Water generated from the filtration process is clearer, odorless, and tasteless.